Effects of The Linguistic Environment on Improving Speech Skill for Female Students of Dar Al-Rahman Institute for Islamic Education - Aslamiah, Nur; Susiawati, Wati; Raswan, Raswan; Muttaqin, Zainal (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
The research aims to prove the role of the linguistic environment in improving the speaking skill of Arabic language learners in official institutions. As well as analyzing how to create a